Characterization of the Ecosystem Services Rendered to the Population by Trees in the City of Parakou in Central Benin - Prucelle Elisee, Zohoun; David Makodjami, Baloubi; Emilia Mawugnon, Azalou-Tingbe; YABI., Ibouraïma. (My University, 2021)
The city of Parakou, like cities in developing countries, is experiencing rapid urbanization with the consequences of the destruction of the tree fabric and the progressive loss of cultural knowledge related to it. But in this city, tree species are spared or planted for several reasons. This paper aims to characterize the ecosystem services associated with these trees according to different social categories of urban dwellers. A sample of 370 inhabitants determined by Dagnelie's formula is used to collect the information. The rate of identification of the types of ecosystem services has been assessed. The analysis of covariance (ANCOVA) was used to analyze the influence of social groups on the rate of identification of services. The characterization of ecosystem services according to the different groups was done using the Correspondence Factor Analysis (CFA). A total of 30 ecosystem services grouped into 24 types in 4 categories, namely provisioning services, regulating services, cultural services and support services were identified. It emerges that the most cited services are respectively, in decreasing order, air regulation (90%), food (86%), aesthetic pleasure (40%) and medicinal virtues (36%). The socio-cultural group and the level of education strongly influence the rate of ecosystem identification. The characterization of ecosystem services by to social groups shows that the interest shown by each social group in ecosystem services depends on the benefits it derives from the tree on a daily basis. Although the population recognizes the services provided by trees, it is not actively involved in their conservation, which justifies the low density of the tree layer in the city of Parakou. This gives rise to research on the socio-economic and institutional constraints linked to the promotion of trees in the city of Parakou.
Keywords: City of Parakou; Trees; Ecosystem Services; Social Groups